The CYP2D6 phenotyping performance of single-point saliva metabolic ratio in a healthy Chinese Han population - Huang, Yongfa; He, Zhangyuting; Guan, Xiaoduo; Hu, Pei; Chen, Rui (Frontiers in Pharmacology, 2025)
The CYP2D6 plays critical roles in drug metabolism, and its inter-individual variability should be properly addressed in clinical practice. Our research aimed to assess the performance of single-point saliva metabolic ratio (MR) in a healthy Chinese Han population using dextromethorphan as the probe drug. MR was determined as the ratio of parent drug to metabolite in 3 h saliva, 3 h plasma, and 0–3 h urine post-ingestion. 416 healthy volunteers were enrolled, with 290 (69.7%) male participants and a median body mass index (BMI) of 23.1 kg/m2. The Spearman correlation coefficients were 0.876 between plasma and saliva MR, and 0.746 between plasma and urine MR. The population was clustered into four metabolizer classes with either plasma or saliva MR, but into two metabolizer classes with urine MR. The saliva-based clustering agreed well with plasma-based clustering (Cohen’s Kappa 0.689). A clear negative correlation was observed between Activity Score (AS) and saliva MR, and linear regression revealed that overweight population had significantly lower saliva MR than others. In conclusion, single-point saliva MR performed better than urine MR with satisfactory correlation with plasma MR and effective separation of four metabolizer classes. Predicting saliva MR with the AS system was more accurate when BMI was considered.